No Nexus between Procedure and Illness: Not a Case of Medical Negligence: NCDRC (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
A case of Keratosis Obturans (wax in ear) was dealt by an ENT surgeon without rupture of tympanic membrane of a female patient aged 12 years. Patient developed signs of meningitis after 11 days and was referred to pediatrician for further treatment by same ENT surgeon. Accordingly, patient was taken to Jeevan Jyot Hospital at Satara on 21.02.2007 where laboratory investigations diagnosed meningitis. After that she was admitted at Chirayu Hospital on 22.02.2007 where another ENT surgeon who opined no rupture of tympanic membrane after various investigations like MRI, Otoscopy, Tympanogram, and impedance audiometry. It was alleged by the patient’s mother (complainant) that after the procedure, patient suffered injury to her right eardrum, which was not properly treated by the Opposite Party (OP) i.e. ENT surgeon. Only a cotton swab was placed inside the ear and a bandage was affixed. Thereafter, the patient was getting headache and pain in her right ear. She approached the OP but he intentionally ignored her therefore she filed a complaint in district forum. District Consumer Dispute Redressal Commission (DCDRC), Satara observed that meningitis was developed either on 20/02/2007 or 21/02/2007 which has resulted from operation of middle ear carried out on 10/02/ 2007. State Consumer Dispute Redressal Commission (SCDRC) overruled decision of DCDRC and dismissed the appeal. National Consumer Dispute Redressal Commission (NCDRC) in revision petition approved the decision of SCDRC that it was a simple case of right Otitis Externa that was aptly dealt with and no direct or related nexus between the initial treatment and procedure undertaken by the OP and the meningitis after 11 days of the initial treatment and procedure is made out.
Keywords: Meningitis; ENT; Pediatrician; Right otitis externa; Tympanic membrane; SCDRC; NCDRC